2018
DOI: 10.1002/cnr2.1125
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human papillomavirus oncoproteins E6 and E7 inhibits invadopodia activity but promotes cell migration in HPV‐positive head and neck squamous cell carcinoma cells

Abstract: Background: The rapid increase in the incidence of head and neck squamous cell car-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 146 publications
0
4
0
Order By: Relevance
“…Nagel et al tested the migratory capacity of several OSCC cell lines using a wound-healing assay and showed that the migratory capacity of HPV-positive cell lines varies and is not signi cantly different from that of HPV-negative SCC cell lines [52]. Similarly, Kahue et al showed that the migratory capacity of HPV-positive OSCC cell lines does not signi cantly differ from the migratory capacity of HPV-negative OSCC cell lines; however, when the expression of E6 and E7 is abrogated in HPV-positive cell lines, their migratory capacity decreases, indicating a potential role of E6 and E7 in migration properties [53]. In our study, differences in cell migration were detected both in in vitro functional assays and at the transcriptome level.…”
Section: Discussionmentioning
confidence: 97%
“…Nagel et al tested the migratory capacity of several OSCC cell lines using a wound-healing assay and showed that the migratory capacity of HPV-positive cell lines varies and is not signi cantly different from that of HPV-negative SCC cell lines [52]. Similarly, Kahue et al showed that the migratory capacity of HPV-positive OSCC cell lines does not signi cantly differ from the migratory capacity of HPV-negative OSCC cell lines; however, when the expression of E6 and E7 is abrogated in HPV-positive cell lines, their migratory capacity decreases, indicating a potential role of E6 and E7 in migration properties [53]. In our study, differences in cell migration were detected both in in vitro functional assays and at the transcriptome level.…”
Section: Discussionmentioning
confidence: 97%
“…Nagel et al tested the migratory capacity of several OSCC cell lines using a wound-healing assay and showed that the migratory capacity of HPV-positive cell lines varies and is not significantly different from that of HPV-negative SCC cell lines [ 60 ]. Similarly, Kahue et al showed that the migratory capacity of HPV-positive OSCC cell lines does not significantly differ from the migratory capacity of HPV-negative OSCC cell lines; however, when the expression of E6 and E7 is abrogated in HPV-positive cell lines, their migratory capacity decreases, indicating a potential role of E6 and E7 in migration properties [ 61 ]. In our study, differences in cell migration were detected both in in vitro functional assays and at the transcriptome level.…”
Section: Discussionmentioning
confidence: 99%
“…SCC-61 cells, an invasive HNSCC cell line originally acquired from the Yarbrough laboratory at our institution, have served as an established cell line model for invadopodia in our laboratory and were cultured as previously described (available from MilliporeSigma, Cat# SCC280, RRID: CVCL_7118). 20,21,24,25 Chemical inhibition of YAP was performed using verteporfin (Sigma) which inhibits YAP/TEAD interactions. 26,27 Kockdown (KD) of YAP was performed using a single ON-TARGETplus siRNA (sequences available from Dharmacon).…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
“…As previously described, statistics were performed using SPSS Software (IBM). 20,21,24,[33][34][35] All data were evaluated for normality with the Shapiro-Wilk or Kolmogorov-Smirnov test. Normal and non-parametric data were then analyzed by the Student's t-test or a Kruskal-Wallis test, respectively, with significance at a p-value < 0.05.…”
Section: Statisticsmentioning
confidence: 99%